PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF EDUCAPLAY TERHADAP HASIL BELAJAR IPAS MATERI AKU DAN KEBUTUHANKU SISWA KELAS IV SD NEGERI PERTIWI LAMGAROT ACEH BESAR - Hasmawati; Mislinawati; Suci Fitriani (STKIP Subang, 2026)
The low learning outcomes of students in IPAS learning are caused by the lack of innovative media utilization, which makes students less enthusiastic and tends to be passive in learning, resulting in only 18 out of 39 students achieving the learning objective attainment criteria of 75. This condition encouraged the researcher to implement Educaplay interactive learning media as a more attractive alternative solution. This study aims to describe the implementation of Educaplay interactive learning media on IPAS learning outcomes of the material